NEW DISTRIBUTIONS OF SOME SPECIES OF EGYPTIAN FLORA - Habeeb, H. R.; EL-Khanagry S.; Mohamed A. (Arab Universities Journal of Agricultural Sciences, 2015)
This research reviews the distribution of some old species of the Egyptian flora in different phytogeographical regions. Results are compared with the suggestions given by Täckholm (1974), El-Hadidi and Fayed (1994/95), El-Khanagry and Mohamed (2004), and Boulos (2009). The research includes new distribution of 38 species belong to 34 genera and 22 families.